A Coefficient Related to Some Geometric Properties of a Banach Space. (5th May 2009) - Zuo, Zhanfei; Cui, Yunan
Abstract : We introduce a new coefficient as a generalization of the modulus of smoothness and Pythagorean modulus of Banach spaceX . Some basic properties of this new coefficient are investigated. Moreover, some sufficient conditions which imply normal structure are presented.